Amor é fogo que arde sem se ver - Marnoto, Rita (2012)
(2012). Amor é fogo que arde sem se ver. In Rita Marnoto (Coord.), Comentário a Camões. Vol. 1. Sonetos (37-50). Lisboa: CIEC, Cotovia. ISBN 978 972 795 330 1